Impact of quality and transparency in scientific writing on the reduction of animal usage in experimental protocols: a review based in pertinent literature - Neves, Matheus M.; Klein, Sandra G.; Silva, Ray C.; Bernardes, Lucas M. M.; Malta, Serena M.; Vieira, Thiago N.; Rosa, Rafael B.; Lima, Isabela L.; Ferreira, Flávia B.; Silva, Murilo V. (Frontiers in Veterinary Science, 2024)
The irreproducibility in scientific research has become a critical issue. Despite the essential role of rigorous methodology in constructing a scientific article, more than half of publications, on average, are considered non-reproducible. The implications of this irreproducibility extend to reliability problems, hindering progress in technological production and resulting in substantial financial losses. In the context of laboratory animal research, this work emphasizes the importance of choosing an appropriate experimental model within the 3R’s principle (Refine, Reduce, Replace). This study specifically addresses a deficiency in data specification in scientific articles, revealing inadequacies in the description of crucial details, such as environmental conditions, diet, and experimental procedures. For this purpose, 124 articles from journals with relevant impact factors were analyzed, conducting a survey of data considered important for the reproducibility of studies. Important flaws in the presentation of data were identified in most of the articles evaluated. The results of this study highlight the need to improve the description of essential information, standardizing studies, and ensuring the reproducibility of experiments in areas such as metabolism, immunity, hormones, stress, among others, to enhance the reliability and reproduction of experimental results, aligning with international guidelines such as ARRIVE and PREPARE.